PEMANFAATAN AUGMENTED REALITY (A PEMANFAATAN AUGMENTED REALITY (AR) DAN VIRTUAL REALITY (VR) DALAM PEMBELAJARAN KIMIA MENGGUNAKAN METODE INTEGRATIVE LITERATUR REVIEW: PEMANFAATAN AUGMENTED REALITY (AR) DAN VIRTUAL REALITY (VR) DALAM PEMBELAJARAN KIMIA MENGGUNAKAN METODE INTEGRATIVE LITERATUR REVIEW - Mulyati Limbong; Chusnur Rahmi (ALOTROP, 2026)
This study aims to analyze the trend of utilizing Augmented Reality (AR) and Virtual Reality (VR) technologies in chemistry learning and to assess their contribution to improving the quality of the learning process. This study uses an integrative Literature Review (ILR) by examining several scientific articles related to the topic discussed. The data used in this study were obtained from research articles found through literature searches using Google Scholar and Semantic Scholar. The articles included in this review are scientific publications equipped with a Digital Object Identifier (DOI) and are relevant to the focus of the study. The selected articles are studies that discuss the use of AR and VR technologies in the teaching and learning process of chemistry, particularly at the secondary education level. The results of the study show that AR technology is widely used in chemistry learning because it can display three-dimensional visualizations of chemical objects. These visualizations help students understand difficult concepts such as molecular structures, chemical reactions, and particle representations, which are often difficult to understand through conventional learning methods. In addition, VR technology provides a more realistic and engaging learning experience through virtual laboratory simulations. Through these simulations, students can conduct practical activities in a safer, more interactive way that closely resembles real laboratory conditions.